Dirty Bertie - Kiss! - MacDonald, Alan 1958- (Stripes, 2011)
Join Bertie as he struggles to escape from the clutches of Angela Nicely, attempts to prove that anything Know-All Nick can do, he can do better, and finds himself surrounded by priceless and wobbly relics at a recording of Antiques Today. Suggested level: primary